Comparison of anthelmintics for pigs raised in outside lots - Allee, G.L.; Schoneweis, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred fifty crossbred pigs averaging 21 lbs. initially were used to evaluate the effects of Banminth or Tramisol on performance of pigs housed in worm-contaminated dirt lots. Neither anthelmintic significantly affected average daily gain or feed efficiency. Pigs fed Banminth continuously were 5% more efficient in feed utilization during the starter phase and 4% more efficient in feed utilization during the grower phase than nonwormed pigs. Pigs fed Banminth had no liver scarring and no ascarids in gastrointestinal tracts at 125 pounds. Untreated pigs and those treated with Tramisol had lever scarring and ascarids in the gastrointestinal tracts at 125 pounds.
Keywords: Swine; Anthelmintics; Banminth; Tramisol; Performance